Comprehensive characterization of monoclonal antibody by Fourier transform ion cyclotron resonance mass spectrometry. Issue 1 (2nd January 2019) - Jin, Yutong; Lin, Ziqing; Xu, Qingge; Fu, Cexiong; Zhang, Zhaorui; Zhang, Qunying; Pritts, Wayne A.; Ge, Ying
ABSTRACT: The pharmaceutical industry's interest in monoclonal antibodies (mAbs) and their derivatives has spurred rapid growth in the commercial and clinical pipeline of these effective therapeutics. The complex micro-heterogeneity of mAbs requires in-depth structural characterization for critical quality attribute assessment and quality assurance. Currently, mass spectrometry (MS)-based methods are the gold standard in mAb analysis, primarily with a bottom-up approach in which immunoglobulins G (IgGs) and their variants are digested into peptides to facilitate the analysis. Comprehensive characterization of IgGs and the micro-variants remains challenging at the proteoform level. Here, we used both top-down and middle-down MS for in-depth characterization of a human IgG1 using ultra-high resolution Fourier transform MS. Our top-down MS analysis provided characteristic fingerprinting of the IgG1 proteoforms at unit mass resolution. Subsequently, the tandem MS analysis of intact IgG1 enabled the detailed sequence characterization of a representative IgG1 proteoform at the intact protein level. Moreover, we used the middle-down MS analysis to characterize the primary glycoforms and micro-variants. Micro-variants such as low-abundance glycoforms, C-terminal glycine clipping, and C-terminal proline amidation were characterized with bond cleavages higher than 44% at the subunit level. By combining top-down and middle-down analysis, 76% of bond cleavage (509/666 amino acid bond cleaved) of IgG1 was achieved. Taken together, we demonstrated the combination of top-down and middle-down MS as powerful tools in the comprehensive characterization of mAbs.